A theory of adults' motivations for learning the African drums in Hong Kong - Lee, Hung Kun (2009)
This study aims at investigating the adults' motivations for participating in organised learning of the African drums in Hong Kong at the turn of the century: how they participate in related learning, why they take part, and how they have developed varied motivations for learning.